Animal Narratology - Jacobs, Joela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Animal Narratology interrogates what it means to narrate, to speak-speak for, on behalf of-and to voice, or represent life beyond the human, which is in itself as different as insects, bears, and dogs are from each other, and yet more, as individual as a single mouse, horse, or puma. The varied contributions to this interdisciplinary Special Issue highlight assumptions about the human perception of, attitude toward, and responsibility for the animals that are read and written about, thus demonstrating that just as "the animal" does not exist, neither does "the human". In their zoopoetic focus, the analyses are aware that animal narratology ultimately always contains an approximation of an animal perspective in human terms and terminology, yet they make clear that what matters is how the animal is approximated and that there is an effort to approach and encounter the non-human in the first place. Many of the analyses come to the conclusion that literary animals give readers the opportunity to expand their own points of view both on themselves and others by adopting another's perspective to the degree that such an endeavor is possible. Ultimately, the contributions call for a recognition of the many spaces, moments, and modes in which human lives are entangled with those of animals-one of which is located within the creative bounds of storytelling.